Tafsir of Alytus — Remarks of the Linguist - Kulwicka-Kamińska, Joanna (Slavistica Vilnensis, 2016)
Tatar translation manuscripts are an extremely interesting subject of interdisciplinary research. They originated in the multicultural and multilingual Grand Duchy of Lithuania (hereinafter referred to as GDL) among Lithuanian and Polish Muslims who lived in a diaspora in Christian surroundings, which had influence on the multifaceted genetics of the Tatar literature, including chronologically and geographically diverse features of the language variety spoken at the Polish-Lithuanian-Belarusian borderland, the connection between the literature of GDL Tartars and Renaissance translations of the Bible into the Polish language, and the Quranic translation tradition reflected in such works as Turkish tafsirs. Moreover, it is possible to indicate common features of Tatar writings and medieval Bible and Psalter literature. One of the oldest monuments of Lithuanian and Polish Muslim literature is the tafsir of Alytus (1723). This paper is a philological study of all language layers of this monument.
Keywords: diachronic and comparative linguistics; theolinguistics; kitab studies; language variety spoken at the Polish-Lithuanian-Belarusian borderland; translation studies